Hoax dan Masyarakat Akademik di Kota Makassar - Wijaya, Zulham; Abdullah, Suparman; Mengge, Buchari; Irsan, Irsan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this research is to understand the process of the academic community being exposed to hoaxes in the city of Makassar. The problem of this research is focused on the process of the academic community exposed to hoaxes? In analyzing the problems raised, the researcher uses an analytical knife from Jean Boudrillar's theory of Hyperreality. Data was collected through observation, in-depth interviews and documentation with qualitative analysis. Determination of informants using purposive sampling in accordance with the classification of informants that have been determined, namely those with Masters and Doctoral education who work as lecturers and actively use social media. The results show that the academic community who actively uses social media has a tendency to use social media to get the latest information in accordance with the interests and paradigms of the academic community.Â  In the information they are interested in, there are hoaxes, facts and opinions which then experience superficial meaning. From any information that has shallow meaning and is reported repeatedly without any comparison news, it will become an accepted truth, including hoax news.